Association of Post Operative Infectious Complications and Length of Hospital Stay with Duration of Surgeries - Ibad Ur Rahman, Muhammad Tahir Ghani, Hafiz Muhammad Ijazulhaq, Muhammad Asad, Hira Jalil, Muhammad Burhanulhaq (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Postoperative infectious complications which results in prolong hospital stay carries a significant risk to patients and burdanise health care system as well. Many risk factors are known to increase the incidence of post operative infectious complications and length of hospital stay. The aim of present study is to determine the association of time duration of surgeries with post operative infectious complications and length of hospital stay. Methodology: This prospective observational study was conducted on 462 patients who underwent various major surgical procedures in the Department of General Surgery in PIMS Hospital, Islamabad from January 2020 to December 2021. Patients <16 years and admitted for trauma were excluded. The time duration of various surgeries from incision to closure was recorded. Post operative complications sepsis, pneumonia, wound infection, urinary tract infection and length of hospital stay was recorded as well. Data was analyzed by spss version 22 .Any Correlation between time duration of surgeries with post operative complications and length of hospital stay determined. Results: Of the total 462 patients who underwent various surgical procedures, the post operative infectious complication rate increased linearly with operation duration at 2.5% per ½ hours ranging from 2.5% to 30.6% in 1 hour to 6 hours respectively. Infectious complications such as UTI, wound infection, pneumonia, and sepsis showed positive correlation with time duration of surgeries. The post operative infectious complications increased after one hour of surgery compared to half hour. Conclusion: As the time duration of surgeries increase the chances of post operative infectious complications also increase, hence increasing the length of hospital stay as well. Keywords: Post operative infectious complications, Hospital stay, Duration of surgeries.